Analisis Kinerja Keuangan Anggaran Pendapatan dan Belanja Daerah (APBD) Kabupaten Pamekasan Tahun 2019 - 2021 - Zuhdi, Fachenda Itsnain Naufal; Mawardi, M. Cholid; Hidayati, Irma (Universitas Islam Malang, 2023)
A company's financial performance is a description of the economic outcomes it can achieve at a given time through its operations. A company's financial performance and decision-making processes will greatly benefit from properly presented information in a financial report. To explore more information contained in the financial statements, an analysis of financial statements is needed. The accountability of local governments in managing regional finances can only be evaluated by measuring financial performance. The financial performance of the Regional Revenue and Expenditure Budget (APBD) in Pamekasan Regency in 2019-2021 is the focus of this study. The subject of this research is the financial performance of Pamekasan District Government. The research object is the Pamekasan Regency APBD realization report for 2019 – 2021. The data analysis method in this study uses quantitative analysis. The results of the research show that the financial performance of regional income and expenditure budgets is generally not good. This is evidenced by (1) the ratio of regional financial independence is very low, namely 8.70%. (2) The regional capability ratio is very low, namely 8.84%. (3) The PAD activity ratio is very effective, namely 113.78%. (4) the ratio of regional original revenue efficiency is less effective because it is only 30.21%.Keywords: Financial performance, revenue budget, expenditure budget, local government financial ratios.